2022
DOI: 10.1002/macp.202100391
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Detection of Aliphatic, Electron‐Rich and Electron‐Deficient Aromatic Volatile Organic Contaminants Using Conjugated Polymeric Fluorescent Nanoaggregates with Aggregation Induced Emission Characteristics

Abstract: Discrimination of aromatic, aliphatic volatile organic compounds (VOCs) with high sensitivity and easy operational techniques is important due to related environmental implications. Herein the development of fluorescent conjugated polymers is reported, consisting of donor-acceptor pairs and their nanoaggregates as fluorophores with differential emission behavior in the presence of aromatic, aliphatic VOCs and electron-deficient VOCs both in aqueous solution and solid state. The polymeric network consists of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Pathak and Sarma et al further synthesized a fluorene-TPE -based conjugated polymer ( C17 ) bearing long hydrophobic alkyl chains, facilitating the interaction of C17 FNPs with VOCs. 241 Likewise, the fluorescence of C17 FNPs and films were quenched by electron-poor VOCs like nitromethane and NB due to PET, enhanced by aliphatic VOCs like cyclohexane because of RIR, while red-shifts from blue to green by aromatic VOCs like mesitylene and toluene were observed owing to conformational changes.…”
Section: Sensing For Environmental Monitoring and Food Safetymentioning
confidence: 98%
“…Pathak and Sarma et al further synthesized a fluorene-TPE -based conjugated polymer ( C17 ) bearing long hydrophobic alkyl chains, facilitating the interaction of C17 FNPs with VOCs. 241 Likewise, the fluorescence of C17 FNPs and films were quenched by electron-poor VOCs like nitromethane and NB due to PET, enhanced by aliphatic VOCs like cyclohexane because of RIR, while red-shifts from blue to green by aromatic VOCs like mesitylene and toluene were observed owing to conformational changes.…”
Section: Sensing For Environmental Monitoring and Food Safetymentioning
confidence: 98%
“…reported VOC sensing using fluorescent CMP nanoparticles prepared from TPE and fluorene building blocks. [ 213 ] CMP nanoparticles of TPEDHF and TPEDDF were prepared by aggregation of corresponding soluble CMPs synthesized via a C─C coupling reaction of tetrabromoniated TPE and dialkyl fluorene diboronic acid. The emission of TPEDHF (λemmax=0.33em$\lambda _{{\mathrm{em}}}^{{\mathrm{max}}} = \ $509 nm) and TPEDDF (λemmax=0.33em$\lambda _{{\mathrm{em}}}^{{\mathrm{max}}} = \ $501 nm) dispersed in water enhanced with the addition of electron‐rich aliphatic VOCs (e.g., cyclohexane, THF, hexane, etc), on the other hand, an additional 30 nm red shift in emission was observed with the addition of aromatic VOCs (e.g., mesitylene).…”
Section: Applications Of Cmps (Powder/thin Films) In Chemical Sensingmentioning
confidence: 99%
“…The reports on CMP-based VOC sensing were mainly centered around tetraphenylethene-based CMPs. [178,207,[209][210][211][212][213] Tetraphenylethene (TPE) is known to adopt a propeller structure wherein the free rotation of phenyl units around the C─C bond results in a non-radiative decay channel and poor emission intensities in solution. [214][215][216] The fluorescence of TPE can be enhanced by the restriction of phenyl rotations either via aggregation, framework integration, or immobilization of molecular TPE and it was thoroughly reviewed in the literature.…”
Section: Cmp Powdersmentioning
confidence: 99%
“…A recent report by Panigrahi et al demonstrated discriminative detection of aliphatic, aromatic VOCs using fluorescent conjugated donor–acceptor-based polymers and their nanoaggregates. 75 The polymeric skeleton consists of a fluorine moiety with dangling alkyl groups as a donor and an AIE, tetraphenylethylene (TPE) core as an acceptor (Fig. 19).…”
Section: Polymersmentioning
confidence: 99%